DETERMINANTS OF ACADEMIC PERFORMANCE OF IN-SCHOOL YOUTH INVOLVED IN CATTLE REARING IN KEBBI STATE, NIGERIA - IBRAHIM, S.; FARINDE, A. J.; NASIRU, S. J. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
The cattle industry in Nigeria is still managed by rearers who do not have formal education despite nomadic education in Nigeria. For the industry's radical transformation in supplying sufficient and affordable animal-source food, there is a need to boost the intellectual capabilities of the youth involved. The study described the respondents' socioeconomic characteristics and evaluated their academic performance. A sample size of 203 was selected to analyse the data collected. Descriptive statistics like frequency counts, mean, and standard deviation were used. Inferential statistics were used to make inferential deductions. The results showed that the mean age of the respondents was 16.95±1.65 years, and the majority (87.2%) were males. Most respondents failed English language, Mathematics, Chemistry, and Physics. The regression results showed the following significant determinants of poor academic performance: the number of siblings (β=-0.252) and cattle herding hours (β =-0.230). ANOVA results showed significant differences (F=4.316) in the academic performance of the sampled respondents. In conclusion, the academic performance of respondents was poor. It is recommended that the number of hours spent herding cattle should be reduced to give them enough time for their academic pursuits.